Women and land rights: The impact of formalization in Tanzania’s Coastal Region - L.A. Fredrick; C. Lucian; J. Urassa (Research in Globalization)
This study investigates the impact of land formalization projects on women’s tenure security in Pangani Ward, Coastal Region, Tanzania, while also considering the broader global implications for women’s land rights. Despite progressive legislation that guarantees equal land rights for women, systemic challenges rooted in socio-cultural norms and economic constraints persist. Using a mixed-methods approach, the research combines qualitative and quantitative data from semi-structured interviews, focus group discussions, and surveys to assess women’s experiences with land formalization. The findings indicate that land formalization has had positive effects, including enhanced tenure security through legal recognition, improved credit access, and reduced land conflicts. However, the study also reveals significant barriers to women’s full engagement in the process, such as declining participation rates, socio-economic inequalities, and deeply ingrained gender biases that limit their ability to exercise land rights fully. These findings are relevant to Tanzania and offer insights into the challenges and opportunities for land rights formalization in other regions globally. The study highlights the need for targeted policy interventions, including increasing women’s participation in formalization processes, providing financial support, and addressing socio-cultural barriers. By examining Tanzania’s experience, this research contributes to a broader global conversation on the intersections of legal frameworks, cultural norms, and economic empowerment, urging a more inclusive approach to land formalization that can support women’s long-term tenure security and improved livelihood outcomes worldwide.